1996
DOI: 10.1002/(sici)1096-9861(19960902)372:4<487::aid-cne1>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic synapses in the antennal lobe and mushroom body of the locust olfactory system

Abstract: To help elucidate the role of inhibitory feedback in the genesis of odour-evoked synchronization of neural activity, we investigated the distribution of gamma-aminobutyric acid (GABA)ergic synaptic terminals in the antennal lobes (AL) and mushroom bodies (MB) of the locust olfactory system. Electron-microscopy, intracellular horseradish peroxidase labelling, and immunocytochemistry were combined to assess the distribution of GABAergic synapses, using established methods (Leitch and Laurent [1993] J. Comp. Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(117 citation statements)
references
References 66 publications
8
109
0
Order By: Relevance
“…The model network consists of 14 identical PNs and 5 identical LNs (which differ only in their random initial condition), thus keeping the ratio between the number of PNs and LNs in the locust (830 and 330 respectively; Leitch and Laurent, 1996). We chose 14 PNs to simulate the activity of the average "Functional Subset" (FS) that was hypothesized to exist in insects (Sivan and Kopell, 2004;Kay, 2004).…”
Section: Network Geometry and Stimulationsupporting
confidence: 88%
“…The model network consists of 14 identical PNs and 5 identical LNs (which differ only in their random initial condition), thus keeping the ratio between the number of PNs and LNs in the locust (830 and 330 respectively; Leitch and Laurent, 1996). We chose 14 PNs to simulate the activity of the average "Functional Subset" (FS) that was hypothesized to exist in insects (Sivan and Kopell, 2004;Kay, 2004).…”
Section: Network Geometry and Stimulationsupporting
confidence: 88%
“…Colocalization with GABA immunostaining Leitch and Laurent (1996) partly reconstructed a giant mushroom body neuron from Bodian's silver-stained preparations and suspected it to be GABAergic. The striking similarity of that neuron with the Mas-ATimmunostained giant mushroom body neuron shown here prompted us to investigate colocalization of GABAand Mas-AT immunoreactivities by immunostaining for GABA and Mas-AT on alternate paraffin sections.…”
Section: Immunostaining In the Midbrainmentioning
confidence: 99%
“…Compared to the other insect species with large numbers of Kenyon cells (Leitch & Laurent, 1996;Neder, 1959;Witthöft, 1967), the advantages of studying the Drosophila MB are its smaller size with a conserved, layered cellular organization (Mobbs, 1984;Rybak & Menzel, 1993;Sjöholm et al, 2006;Strausfeld, 2002;Strausfeld et al, 2003) and its amenability to genetic manipulation (Venken & Bellen, 2005). This allows counting, rather than only estimating, the total number of Kenyon cells, and indeed, various studies have reported total numbers based on direct counting or extrapolation (Balling et al, 1987;Hinke, 1961;Ito & Hotta, 1992;Mader, 2004;Technau & Heisenberg, 1982;Technau, 1984).…”
Section: Introductionmentioning
confidence: 99%